An M2M gateway-centric architecture for autonomic healing and optimising of machine-to-machine overlay networks. (2017) - Dhraief, Amine; Belghith, Abdelfettah; Mathkour, Hassan; Drira, Khalil
The machine-to-machine (M2M) technology, is expected to be one of the most promising revenue-generating services. However, to ensure the wide spread of this technology, M2M communications should be secure, fault-tolerant and self-managed. In this work, we add to the M2M gateway the self-healing and self-optimising autonomic capabilities. We couple at the M2M gateway level the host identity protocol (HIP) with the reachability protocol (REAP). REAP enables a selfhealed M2M communication as it detects possible failures and rehomes an M2M session to a new overlay path. We modify REAP to ensure self-optimised M2M communications. REAP continuously monitors M2M overlay paths and always selects the best available ones. We implement our solution on the OMNeT++ simulator. Results show that M2M sessions effectively resume after an outage. Results also highlight that M2M sessions autonomically select the best available M2M overlay paths.